Frequency of Hyperlipidemia in Type 2 Diabetes Mellitus Patients with Microalbuminuria - Maeda Jabeen; Sehrish Kanwal; Jamal Waris; Asad Sufain Azeem; Kahlid Ibrahim Ahktar; Amna Nasar (Pakistan Armed Forces Medical Journal, 2024)
Objective: To evaluate the frequency of hyperlipidemia in type 2 diabetes mellitus (DM) patients with microalbuminuria attending a tertiary care hospital.